First–principles study of potassium adsorption and diffusion on graphene. (2nd January 2020) - Yang, Junwei; Yuan, Yanhong; Chen, Guohong
Abstract : Potassium–ion batteries (KIBs) are a new–type of energy storage devices that have attracted increasing attention due to their low cost and the abundant resource of K in the Earth's crust. Monolayer and multilayer graphene are promising electrode materials for KIBs. Herein, the adsorption and diffusion of potassium atoms on the surface of graphene were studied using the first–principles calculations including the van der Waals interaction. It was determined that K atoms can stably adsorb on the surface of graphene. The climbing image nudged elastic band method was employed to calculate the diffusion barriers of a single K atom and two K atoms on the surface of graphene. The results demonstrated that the diffusion barrier of a single K atom on graphene was low. The interaction between K atoms was considered and it facilitates the K atom diffusion to the second and third nearest–neighbour site of the K adatom, but prevents the K atom diffusion to the far nearest–neighbour site of the K adatom. Moreover, the difference in charge density demonstrates that there was a significant charge transfer from two K adatoms to its nearest–neighbour carbon atoms. GRAPHICAL ABSTRACT: